Gambaran Tingkat Kejadian Anemia Dan Perkembangan Balita Usia 6 - 60 Bulan - Endah Puji Astuti; Ratna Prahesti; Ana Dwi Andriyani (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2016)
In Indonesia, there are more than half of under-five children suffer from malnutrition resulting in growth retardation, the decrease of cognitive function, psychomotor and the immune system of children. These problems occur because children suffering from malnutrition will experience lack of energy and protein as well as the shortage of some important micronutrients. The purpose of the research to know the description of the development of toddlers and the incidence rate of anemia on the group. This was an analytical- correlation research which involved a cross sectional approach. The population of the research included 603 toddlers aged 6 months-5 years old with research samples by 158 toddlers taken by purposive sampling. The primary data were collected using Denver Development Screening Test (DDST) dan Digital Haemoglobin Test. The analysis used Kendall’s tau. The result showed that 49,4% of toddlers suffered from mild anemia, and 69,6% of them had normal development. The majority of toddlers suffering from anemia also had normal development.